Three-dimensional femtosecond laser processing for lab-on-a-chip applications - Sima Felix; Sugioka Koji; Vázquez Rebeca Martínez; Osellame Roberto; Kelemen Lóránd; Ormos Pal (Nanophotonics, 2018)
The extremely high peak intensity associated with ultrashort pulse width of femtosecond laser allows us to induce nonlinear interaction such as multiphoton absorption and tunneling ionization with materials that are transparent to the laser wavelength. More importantly, focusing the femtosecond laser beam inside the transparent materials confines the nonlinear interaction only within the focal volume, enabling three-dimensional (3D) micro- and nanofabrication. This 3D capability offers three different schemes, which involve undeformative, subtractive, and additive processing. The undeformative processing preforms internal refractive index modification to construct optical microcomponents including optical waveguides. Subtractive processing can realize the direct fabrication of 3D microfluidics, micromechanics, microelectronics, and photonic microcomponents in glass. Additive processing represented by two-photon polymerization enables the fabrication of 3D polymer micro- and nanostructures for photonic and microfluidic devices. These different schemes can be integrated to realize more functional microdevices including lab-on-a-chip devices, which are miniaturized laboratories that can perform reaction, detection, analysis, separation, and synthesis of biochemical materials with high efficiency, high speed, high sensitivity, low reagent consumption, and low waste production. This review paper describes the principles and applications of femtosecond laser 3D micro- and nanofabrication for lab-on-a-chip applications. A hybrid technique that promises to enhance functionality of lab-on-a-chip devices is also introduced.